Does managerial power increase selective hedging? Evidence from the oil and gas industry - Håkan Jankensgård (Journal of Risk and Financial Management, 2019)
This study examines the managerial power-hypothesis of selective hedging, which holds that selective hedging is observed more frequently in companies where managers have greater latitude to execute hedging proposals without serious scrutiny or questioning. The hypothesis is tested using hand-collected data on corporate governance and derivative positions from the oil and gas industry. The results support the view that managerial power increases selective hedging. The main governance dimension associated with selective hedging is the extent of inside ownership. Firms with high inside ownership have excessive variability in their derivative portfolios, were more prone to opportunistic behavior following the great rise in the oil price in the mid-2000s, and have lower realized cash flow from hedging.
Keywords: G30; G32; 330; selective hedging; agency costs; corporate governance; inside ownership